2015
DOI: 10.1038/srep17610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Refractive Error on the Melanopsin Mediated Post-Illumination Pupil Response (PIPR)

Abstract: Melanopsin containing intrinsically photosensitive Retinal Ganglion cells (ipRGCs) mediate the pupil light reflex (PLR) during light onset and at light offset (the post-illumination pupil response, PIPR). Recent evidence shows that the PLR and PIPR can provide non-invasive, objective markers of age-related retinal and optic nerve disease; however there is no consensus on the effects of healthy ageing or refractive error on the ipRGC mediated pupil function. Here we isolated melanopsin contributions to the pupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
107
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 45 publications
(66 reference statements)
13
107
0
4
Order By: Relevance
“…The data were fitted with linear and exponential models Zele et al 2011) and analyzed according to our established protocols (Adhikari et al 2015b). To control for individual differences in resting pupil diameter, all data are reported as a percentage of the resting baseline pupil diameter (average pupil diameter during 5 s pre-stimulus period) (Adhikari et al 2015a;Adhikari et al 2015b); a larger percentage value indicates smaller constriction amplitude. The PIPR was quantified at six seconds after light stimulus offset (Park et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were fitted with linear and exponential models Zele et al 2011) and analyzed according to our established protocols (Adhikari et al 2015b). To control for individual differences in resting pupil diameter, all data are reported as a percentage of the resting baseline pupil diameter (average pupil diameter during 5 s pre-stimulus period) (Adhikari et al 2015a;Adhikari et al 2015b); a larger percentage value indicates smaller constriction amplitude. The PIPR was quantified at six seconds after light stimulus offset (Park et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…To assess ipRGC function we measured the melanopsin mediated PIPR using customized paradigms developed in our laboratory (Adhikari, Pearson, Anderson, Zele & Feigl 2015a;Adhikari et al 2015b;Feigl et al 2011b;Maynard et al 2015) with high irradiance stimuli designed for use with the RAPDx pupillographer (Konan Medical USA, Inc., Irvine, CA). IpRGCs produce a sustained pupil constriction after offset of short wavelength light known as the post-illumination pupil response (PIPR) (Gamlin et al 2007;Kawasaki & Kardon 2007;Markwell et al 2010), which is absent with presentation of long-wavelength stimuli that have low melanopsin excitation.…”
Section: Pupillometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a constant retinal irradiance cannot be achieved under a closed-loop condition without the use of pharmacological pupil dilation (Loewenfeld et al, 1993). Since, a Newtonian view pupillometer projects a divergent beam under a closedloop condition, preclinical changes in the pupil responses may be harder to detect given the controlled retinal illumination can only be achieved with a pharmacological dilated pupil that allows for the measurement of the largest consensual pupillary response (Adhikari, Pearson, Anderson, Zele, & Feigl, 2015a). An open-loop condition allows a complete entry of the light into the eye without iris shading (Loewenfeld et al, 1993) and can be achieved by using a Maxwellian view system (Loewenfeld et al, 1993) that focuses the light beam on a small area of the pupil to ensure the complete entry of the light irrespective of the pupil size (Westheimer, 1966).…”
Section: Figurementioning
confidence: 99%
“…Hence, it has been suggested that melatonin may play a role in eye growth and development, and could be involved in the regulation of diurnal rhythms associated with ocular growth. However, a recent cross-sectional study on healthy adult humans (age range: 21 -70 years) found that melanopsin mediated pupil responses were not significantly different between emmetropes and myopes (Adhikari et al, 2015). Further research is required to understand the relationship between habitual light exposure and diurnal rhythms and eye growth, and to understand the relationship between diurnal rhythms and longer-term eye growth in humans.…”
mentioning
confidence: 99%